2023
DOI: 10.1021/acsanm.3c01509
|View full text |Cite
|
Sign up to set email alerts
|

Size and Morphology Modulation in ZnO Nanostructures for Nonlinear Optical Applications: A Review

Abstract: Morphology-rich ZnO as a direct band gap II−VI semiconductor is a promising material for photonic, optical, and electronic devices. Nanostructured materials have provided a leading edge to the next-generation technology due to their distinguished performances and efficiencies for device fabrication. The nonlinear optical (NLO) properties and mechanisms dependent on the size and dimensionality of ZnO nanostructures remain to be elucidated. Herein, we begin to provide a comprehensive summary of the status of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 606 publications
0
7
0
Order By: Relevance
“…ZnO morphology is vital for adjusting the photocatalytic performance. 35 Therefore, the photocatalytic activity of the ZnO@CNF nanocomposites towards MO degradation was determined by using blue light as the energy source. Pristine CNF showed negligible MO degradation efficiency (2.0%) and served as a blank control.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO morphology is vital for adjusting the photocatalytic performance. 35 Therefore, the photocatalytic activity of the ZnO@CNF nanocomposites towards MO degradation was determined by using blue light as the energy source. Pristine CNF showed negligible MO degradation efficiency (2.0%) and served as a blank control.…”
Section: Resultsmentioning
confidence: 99%
“…During the boom in nanoscience and nanotechnology, ZnO has been proven to be the richest in morphological diversity that plays a significant role in tuning the physicochemical characteristics at the nanoscale dimensions. A wide gamut of nanostructures with versatile geometries, such as zero-, one-, two-, and three-dimensional nanostructures, have been synthesized/fabricated because of the simplicity in the process of crystallization and anisotropic growth behavior . Zero-dimensional ZnO materials, such as quantum dots, nanospheres, nanoballs, etc., exhibit the abundance of grain boundaries, and as a consequence, these materials exhibit higher solubility as well as higher dissolution rates in comparison with bulk counterparts .…”
Section: Synthesis/fabricaion Of Zno Crystalsmentioning
confidence: 99%
“…The growth of the bunches of ZnO nanoflowers that occurs along the (0001) crystallographic orientation results into the formation of flower-like structures . It has also been observed that the growth of ZnO nanowires and faceted nanotubes occurs along the [0001] direction ( c -axis) and they are enclosed by {100} surfaces, while the direction of growth of the ZnO nanoporous belts occurs parallel to the (0001) plane . It has also been revealed that the Zn-terminated (0001) surface can be stabilized through the spontaneous formation of a higher concentration of Zn-deficient pits of triangular shape and step edges that can be terminated with coordinated O atoms.…”
Section: Morphological Transformationmentioning
confidence: 99%
See 2 more Smart Citations